Design and implementation of smart transport monitoring system to ensure passenger's safety - Aman, Anika Binte; Nawar, Nushin; Hossain, Safayed Maruf; Hossain, MD. Zakir (Brac University, 2024)
This final year design project is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2023.